2015
DOI: 10.3390/nu7075235
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Psychosis: Confirmation of a New Clinical Entity

Abstract: Non-celiac gluten sensitivity (NCGS) is a syndrome diagnosed in patients with symptoms that respond to removal of gluten from the diet, after celiac disease and wheat allergy have been excluded. NCGS has been related to neuro-psychiatric disorders, such as autism, schizophrenia and depression. A singular report of NCGS presenting with hallucinations has been described in an adult patient. We report a pediatric case of a psychotic disorder clearly related to NCGS and investigate the causes by a review of litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 31 publications
3
44
0
1
Order By: Relevance
“…The girl refused to continue the gluten challenge and went back to the GFD, with a complete and persistent regression of all symptoms within 1 week. Our case report confirms the existence of 'gluten psychosis' as a possible manifestation of NCGS [38] .…”
Section: Ncgs and Other Psychiatric Disorderssupporting
confidence: 84%
“…The girl refused to continue the gluten challenge and went back to the GFD, with a complete and persistent regression of all symptoms within 1 week. Our case report confirms the existence of 'gluten psychosis' as a possible manifestation of NCGS [38] .…”
Section: Ncgs and Other Psychiatric Disorderssupporting
confidence: 84%
“…Moreover, it has been proposed that gluten causes depression, anxiety, autism and schizophrenia in patients with NCGS [109], and also reported that psychosis might be a manifestation of NCGS [110]. …”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%
“…Significant improvement was described in two patients with schizophrenia [109], and in two with dementia [110]. Complete remissions were described in three different patients with psychotic symptoms [111,112,113].…”
Section: The Role Of Diet In the Therapymentioning
confidence: 97%
“…Znacząca poprawa opisana została u dwóch pacjentów ze schizofrenią [109] oraz u dwóch z otępieniem [110]. Pełne remisje opisane zostały u trzech różnych pacjentów z objawami psychotycznymi [111,112,113].…”
Section: Rola Diety W Leczeniuunclassified